Impacto de la publicidad creativa y su efecto en la acción de compra en el sector automotriz de Lima Metropolitana - Reyes Guzmán, Andrea Selena (2023)
Many companies, agencies, and society as a whole have a keen interest in creative advertising. When developed correctly, it can yield significant benefits by informing, persuading, and leaving a lasting impression, depending on the intended approach. However, it is important to note that in today's highly visual world, where advertising is omnipresent, viewers are more selective, avoiding ads that do not appear attractive or relevant. The automotive industry, known for its substantial advertising expenditure to capture public attention, faces a competitive environment that demands extra effort and strategic planning to make an impact. This research focuses on defining creative advertising and exploring how it can serve as a powerful tool across various economic sectors, particularly the automotive industry. Furthermore, given the current state of the automotive industry, heavily impacted by the global pandemic, and faced with constantly shifting consumer behavior and increasing competition, it is crucial for the industry to reinvent itself and seek new creative approaches to engage consumers. Thus, the industry must go beyond mere image recall and utilize disruptive elements that break away from the conventional advertising practices. Consequently, this research aims to investigate whether presenting creative advertisements to customers can effectively generate purchase actions. The study centers around the five key elements of creative advertising: flexibility, elaboration, synthesis, originality, and artistic value. By examining the impact of creative advertising on purchase actions, the research seeks to determine its efficacy in connecting with customers and driving desired outcomes.